The very high energy gamma ray burst GRB190114C as observed by MeerKAT - Diretse, Reikantseone (Department of Astronomy, 2025)
We present the MeerKAT study of the highly energetic gamma ray burst (GRB), GRB190114C, which was the first GRB to have been recorded at teraelectronvolt (TeV) energies by the MAGIC telescope. We have observed this GRB with MeerKAT from as early as within the first day of the burst event, up to nearly a year at over 350 days. Our 13 epoch light curve is the most sampled radio light curve of this GRB at low frequencies (1.28 GHz) in comparison to published results. We detail the evolution of GRB190114C as a forward shock in a homogeneous medium for about 100 days post-burst, followed by a jet-break likely occurring simultaneously with the passage of the characteristic peak frequency across our observing band. We constrain the host galaxy component, and compare our modelled host value to fluxes extrapolated from pre-burst images of the field. As it is often for GRB observations at low radio frequencies, the evolution of GRB190114C is highly affected by strong interstellar scintillation, which we quantitatively constrain as long lasting refractive scattering. We then use the calculated scintillation parameters to put an upper limit on the radial size of the fireball, and compare this to other GRBs. Beyond the GRB, we take a commensal approach to study its intriguing and expansive background. We survey the field for potential radio transients or variables. We apply the LOFAR Transients Pipeline (TraP) in this pursuit. The pipeline has been adapted for MeerKAT data. We discover 11 potential transient or variable candidates. We detail their light curves, images, multi-wavelength counterparts and classifications to reveal their nature. We find that most of the candidates we find are likely active galactic nuclei (AGNs), and their variability in this context is reasonably due to interstellar scintillation as derived for the field